The influence of the U.S. export controls against China on the resilience of Chinese corporates - Huan He; Peng Chen; Xianjing Huang; Le Li (PLoS ONE, 2025)
As Sino-US trade frictions intensify, the United States has continually strengthened its export control measures against China, posing potential risks to the international supply chains and production operations of Chinese enterprises. This paper has compiled data from the U.S. Bureau of Industry and Security (BIS) Entity List and employed A-share manufacturing listed companies in China from 2015 to 2023 as research samples. By treating the U.S. export controls against China as a quasi-natural experiment, we employ a multi-period difference-in-differences model to analyze the impact of these export controls on the resilience of Chinese manufacturing listed companies and the underlying mechanisms. Our findings reveal that U.S. export controls significantly reduce the resilience of affected firms within the industry in China, primarily by inhibiting internationalization processes, exacerbating financing environments, and intensifying corporate risks. Further analysis shows that firms with higher product market competitive advantages, greater analyst coverage, and more aggressive development strategies are better equipped to mitigate the shocks of export controls. Conversely, firms lacking political connections or operating in environments with higher external uncertainties are more susceptible to negative impacts, with their resilience significantly diminished. This study broadens the research scope of international trade policies and corporate resilience, offering insights for Chinese enterprises to enhance their adaptive capabilities and optimize business strategies in the complex and volatile international trade environment.